BOOSTING THE STUDENTS IN MASTERING WRITING SKILL THROUGH THE IMPLEMENTATION OF PPIE (POINT, PRESENTATION, ILLUSTRATION, EXPLANATION) TECHNIQUE - Zuraini Zuraini; Misnawati Misnawati; Asruna Lisa; Eli Nofriati (Jurnal CULTURE (Culture, Language, and Literature Review), 2021)
Abstract People need to learn writing in English for occupational or academic purpose to write well, students must have good capabilities in writing process and aspects of writing. The purposes of the research are: to improve PPIE technique for the students writing skill in Narrative text. And to know the students’ response of PPIE Technique in Narrative text. Qualitative and quantitative research methodology were combined by the researcher. In qualitative, the researcher used questionnaires, observation sheet as instrument of the research to observe and learn. Based on the quantitative research methodology, the researcher and teacher gave post-tes. The result of observation sheet for the teachers performance in cycle 1 had the mean score was about 67.84% . In cycle 2 showed that the the mean score was about 83.14%. The result of observation sheet for the students’ activities in cycle 1 the mean score was 52.54%. In second cycle mean score was 75.68%. The total score on questionaires about 12.99 and average score about 3.24. Therefore, the researcher concluded that the PPIE technique could improve the students’ ability in writing skill.